Lifetime History of Suicide Attempts among Not Guilty by Reason of Insanity State Hospital Inpatients: The Roles of past Harmful Substance Use and Current Social Support. Issue 4 (1st October 2020) - Mitchell, Sean M.; Brown, Sarah L.; Scanlon, Faith; Swogger, Marc T.; Delgado, Darci; Ventura, Maria I.; Bolaños, Angelea D.; Morgan, Robert D.
Abstract: This study tested current perceived social support (CPSS) as a moderator of the relation between previous substance use (PSU) and lifetime suicide attempt (SA) history among 200 NGRI inpatients. Results indicated no significant CPSS main effect. PSU was associated with greater odds of multiple prior lifetime SA. Moderation indicated those low in PSU but high in CPSS were least likely to report multiple prior lifetime SA. Conversely, NGRI inpatients with high CPSS and high PSU were most likely to report multiple lifetime SA. Our study suggests CPSS and PSU assessments may inform suicide risk assessments and interventions among NGRI inpatients.